High cycle life all-solid-state fluoride ion battery with La2NiO4+d high voltage cathode - Mohammad Ali Nowroozi (Nature Portfolio, 2020)
Fluoride ion batteries receive substantial interest, but are limited by their cyclic performance. Here, an La2NiO4.13 cathode in an all-solid-state fluoride ion battery achieves up to 220 cycles for a 30 mAh/g cut-off capacity.